Access to Education in Indonesia's 3T Regions: Infrastructure Challenges and Technological Solutions - Risyad Fahriz Husaini; Sindi Aprilianti; Riefa Maulya Nuryani; Laela Istiqomah; Yulianah Yulianah; Riztrya Novedliani (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to identify educational barriers in Indonesia's Frontier, Outermost, and Disadvantaged (3T) regions and analyze technology-based strategies that may support educational equity. Research Method: A qualitative library research approach with descriptive-analytical content analysis was employed. Data were collected from peer-reviewed articles, government reports, and policy documents published between 2021 and 2026 using predefined inclusion criteria to ensure source relevance and credibility. Results and Discussion: The findings indicate that educational inequality in 3T regions is shaped by limited internet connectivity, inadequate electricity infrastructure, geographical isolation, restricted access to digital devices, and low digital literacy among educators. Technology-based interventions, including satellite internet, offline learning platforms, alternative energy systems, and teacher capacity-building programs, show potential to improve educational access; however, their effectiveness depends on contextual readiness, sustainability, and policy support. Implications: Educational transformation in 3T regions requires integrated efforts that combine infrastructure development, human capacity strengthening, and responsive policy frameworks. Originality: This study proposes an integrative perspective that positions infrastructure readiness, human capacity, and policy support as interconnected determinants of sustainable educational digitalization in 3T regions.